Cytochrome P450 3A1 mediates 2,2',4,4'-tetrabromodiphenyl ether-induced reduction of spermatogenesis in adult rats. - Zhan Zhang (Public Library of Science (PLoS), 2013)
Background 2,2',4,4'-tetrabromodiphenyl ether (BDE47) is the dominant PBDE congener in humans, wildlife, and the environment. It has been reported to be metabolized by cytochrome P450 (CYP) enzymes. Still, the effects of BDE47 on spermatogenesis failure are attracting an increasing amount of attention. However, it is unclear whether CYP-mediated metabolism contributes to BDE47-induced reproductive toxicity. Methodology and principal findings The role of cytochrome P450 3A1 (CYP3A1) in the formation of oxidative metabolites of BDE47 and its induced spermatogenesis failure was investigated in SD rats. BDE47 significantly increased the expression and activity of CYP3A1 in rat liver, and 3-OH-BDE47, the major oxidative metabolite of BDE47, dose-dependently increased in rat liver, serum, and testis, which was aggravated by dexamethasone (DEX), an inducer of CYP3A1. Additionally, testicular 3-OH-BDE47 and reactive oxygen species (ROS) in seminiferous tubules increased especially when BDE47 was administered in combination with DEX, which was confirmed in GC-1 and GC-2 cells that 3-OH-BDE47 induced more ROS production and cell apoptosis via the upregulation of FAS/FASL, p-p53 and caspase 3. As a result, daily sperm production dose-dependently decreased, consistent with histological observations in giant cells and vacuolar spaces and increase in TUNEL-positive apoptotic germ cells. Conclusion CYP3A1-mediated metabolic activation of BDE47 and the active metabolite 3-OH-BDE47 and consequent ROS played an important role in reduction of spermatogenesis by germ cell apoptosis. Our study helps provide new insights into the mechanism of reproductive toxicity of environmental chemicals.